The Role of Intercellular Adhesion Molecule-1 in the Pathogenesis of Psychiatric Disorders - Müller, Norbert (Frontiers in Pharmacology, 2019)
Inter cellular adhesion molecule-1 (ICAM-1) is a transmembrane glycoprotein that is overexpressed in many pathological states. Although, like many other immune molecules, ICAM-1 plays only a limited role in the abundant concert of the immune response, it may be more important than we realize. In the central nervous system (CNS), ICAM-1 is expressed in microglial cells and astrocytes and in endothelial cells in the white and gray matter of the human forebrain. It is of particular interest in psychiatric disorders for two reasons: It has a key function for the blood-brain barrier, which plays an important role in the biology of psychiatric disorders, and it is a marker for inflammation. Although the blood level of soluble ICAM-1 (sICAM-1) might be lower in acute unmedicated schizophrenia, it has been reported to be increased in many other psychiatric conditions, such as major depression, bipolar disorder, and dementia. In bipolar disorder, high sICAM levels were found during both the depressed and the manic state and also during the euthymic phase (the free interval), possibly indicating that sICAM is a trait marker. High sICAM-1 blood levels have also been found in depression comorbid to a somatic disease state. Interestingly, sICAM-1 levels also increase during aging. Some studies investigated sICAM-1 levels in the cerebrospinal fluid (CSF) of psychiatric disorders and ICAM-1 expression in postmortem CNS tissue of psychiatric patients and found that the overall duration and duration of the chronic phase of the psychiatric disorder seem to play a role in both. Moreover, confounders, such as antipsychotic and antidepressive medication, have to be considered. sICAM-1 levels seem to be associated with hypopermeability or hyperpermeability of the blood-brain barrier and thus to influence the communication between the CNS immune system, represented by glia cells, and the peripheral immune system. The balance between the influx and efflux of immune molecules into and out of the CNS may be one of the pinpoints in psychiatric disorders, in particular in the chronic phase, e.g. in schizophrenia. This aspect, however, needs further intense research, in particular to enable researchers to develop therapeutic principles based on an immune/inflammatory approach.